The Simulation of Transient Heat Transfer in a Thermal Boundary Layer - Tan, Kah Yaw (1999)
The onset of convection in a horizontal layer is widely recognised as the simplest example of hydrodynamic instability where nonlinear temperature profile prevails. A newly defined transient Rayleigh number that incorporates the mode of heat transport and the critical time can be used to predict the onset of convection. The mode of heat transport is characterized by a thermal boundary condition that determines the Biot number and its corresponding critical Rayleigh number. The study of onset of convection can be verified by using Computational Fluid Dynamic (CFD) to solve the governing partial differential equations for heat conduction, momentum, energy and chemical species. The simulation of heat transfer in the thermal layer was carried out by the commercial software, FLUENT. The occurrence of the convection was observed for two boundary conditions: constant heat flux and fixed surface temperature. Most of the observed values were in good agreement with the theoretical values. The critical time and critical depth for transient heat transfer can be determined accurately. However, the accuracy of modeling of transient heat transfer can be further improved.